Effect of Extracts from Dominant Forest Floor Species of Clear-Cuts on the Regeneration and Initial Growth of Pinus sylvestris L. with Respect to Climate Change - Vaida Sirgedaitė-Šėžienė; Adas Marčiulynas; Virgilijus Baliuckas (Plants, 2021)
Climate change influences the ecological environment and affects the recruitment of plants, in addition to population dynamics, including Scots pine regeneration processes. Therefore, the impact of cover-dominant species extracts on the germination of pine seeds and morpho-physiological traits of seedling under different environmental conditions was evaluated. Increasing temperature reinforces the plant-donor allelochemical effect, reduces Scots pine seed germination, and inhibits seedling morpho-physiological parameters. Conditions unfavourable for the seed germination rate were observed in response to the effect of aqueous extracts of 2-year-old Vaccinium vitis-ideae and 1-year-old Calluna vulgaris under changing environmental conditions. The lowest radicle length and hypocotyl growth were observed in response to the effect of 1-year-old C. vulgaris and 2-year-old Rumex acetosella under increasing temperature (+4 °C) conditions. The chlorophyll a + b concentration in control seedlings strongly decreased from 0.76 to 0.66 mg g−1 (due to current environmental and changing environmental conditions). These factors may reduce the resistance of Scots pine to the effects of dominant species and affect the migration of Scots pine habitats to more favourable environmental conditions.